Long-Term Land Use Land Cover Change in Urban Centers of Southwest Ethiopia From a Climate Change Perspective - Dessu, Tesfaye; Korecha, Diriba; Hunde, Debela; Worku, Adefires (Frontiers in Climate, 2020)
Long-term urban land use land cover change (LULCC) dynamics and climate change trends of Southwest Ethiopia’s four urban centers were examined for sixty years. Remote sensing, aerial photos, and Landsat, temperature, and rainfall data were analyzed from a climate change perspective over Jimma, Bedelle, Bonga, and Sokorru towns of southwest Ethiopia from 1953 to 2018. Based on geospatial analysis and maximum likelihood supervised image classification techniques to classify LULCC categories, the Mann-Kendall test was applied to perform trend analysis on temperature and rainfall. The LULCC analysis revealed that built-up areas over the urban centers had shown an increasing trend with the highest increment by 2360 hectares over Jimma, while vegetation, wetland, and cropland declined due to conversion of plain lands to built-up areas and other uses. The pronounced decline of vegetation coverage was noticed in Jimma, Bedelle, Bonga, and Sokorru by 1427, 185,116, and 32 hectares, respectively. Mann-Kendall test results showed a significant sign of intra-seasonal and inter-annual variability of rainfall while the summer and annual rainfall patterns remained less variable compared to other seasons. This study's findings revealed that when the mean between two climatic normals of 1953-86 is compared with 1987-2018, the temperature has significantly increased in the latter three decades. The rapid expansion of built-up areas coupled with a sharp decline of green space or vegetation and agricultural/croplands could lead to gradual changes in LULCC classes, which have contributed to the changing of local climate, especially the surface temperature and rainfall over the urban centers of southwest Ethiopia. Therefore, we recommend that the local urban administrations emphasize sustainable urban development by integrating urban planning policies with land use to protect the environment by adapting local municipal adaptation and national climate change strategies. Restoration of the local environment and creation of climate-smart cities could be critical to the resilience of urban dwellers and ecosystems to the changing climate by enhancing grass-root climate services. To that end, we recommend further advanced research to understand how urban LULC-related changes and other factors contribute to local climates as urban centers of Southwest Ethiopia are undergoing a rapid transformation towards rural surroundings.